Teacher Class Management Ability in the Teaching and Learning Process in Grade V SD Negeri 153069 Pinangsori 2 - Henny Herliny Pangaribuan; Nurul Hasanah Nasution; Rosari Hasianna Sagala; Try Yeni Veronica Zega; Yunita Purba (Formosa Journal of Science and Technology, 2023)
This study aims to evaluate the teacher's role in classroom management and observing student behavior at SD Negeri 153069 Pinangsori 2. The case study approach is used by collecting data through observation and interviews. The results of the study show that teachers have succeeded in implementing classroom management well, understanding student characteristics, providing guidance, and organizing learning activities. The teacher also acts as a motivator and advisor for students. Student behavior shows good quality, with enthusiasm in learning and acceptance of the teacher. Assessment is carried out through pretest and posttest to measure student understanding. This research suggests that teachers continue to improve skills in classroom management and provide appropriate feedback to students. In conclusion, teachers have an important role in creating an effective and efficient learning environment and developing positive student behavior.